Paradoxes of Nostalgia Cold War Triumphalism and Global Disorder since 1989 - Von Eschen, Penny M. (American Encounters/Global Interactions, 2022)
Penny M. Von Eschen offers a sweeping examination of the afterlife of the cold war and its lingering shadows, showing how a nostalgia and longing for stability fuels US-led militarism and the rise of xenophobic right-wing nationalism and authoritarianism around the world.